A Stochastic Inventory Model Incorporating Intra-Year Purchases and Accounting Tax Incentives - Biddle, Gary C.; Martin, R. Kipp (Management Science, 1986)
It has been observed that firms alter year-end inventory policies in response to accounting tax incentives. This study proposes a stochastic ordering policy model which quantifies these effects. An innovative feature is its use of two decision variables: an initial order-up-to-level at the beginning of each year and a desired year-end inventory level. The ability to place a second order after demand has been assessed allows for an explicit consideration of the effects of tax incentives on order quantity decisions. Separate formulations are developed for the two most widely-used inventory accounting methods, LIFO and FIFO. The model provides new implications for choices between LIFO and FIFO, the forms of optimal ordering policies under each and for year-end inventory levels. A procedure is given for calculating the optimal FIFO policy. Calculating optimal LIFO policies is very difficult so myopic approximate policies are given which bound the optimal policy.